Management control systems and innovation: A case study grounded in institutional theory - Barros, R. S.; Ferreira, A. (Journal of Management Control, 2023)
Drawing on the growing literature that has addressed the role of Management Control Systems in innovation and the literature on institutional theory, this study explores the case of Amorim Cork Composites to analyse how the situated rationalities within the company get reflected in the management control practices in use, and then how these practices are used to communicate and provide guidance when innovation is part of the strategy. The study uses a single case study approach at an innovative company, collecting data from 32 interviews, direct observations, and documentation of the company. Based on that data, this study is able to perceive the existence of a rationality that is constructed around the importance of innovation, which becomes a paramount part of the defined strategy and leaves signs on to the internal control practices of the company. After that, through a mix of strategic objectives, well-defined cascaded process of these objectives, values, mottos, objectives related to that situated rationality within the company, and with the commitment created within the “signing” of objectives contracts, managers are able to communicate strategically and provide guidance to the collaborators, driving them to action that makes them more aware.